An analysis of discharge and water quality of an urban river and implications for stormwater harvesting - Aziz, Fahad (Department of Environmental and Geographical Science, 2021)
Development in urban catchments often result in rivers being converted into large stormwater canals where stormwater is removed as quickly as possible to prevent flooding. A combination of elevated peak flows, increased nutrients and contaminants and reduced biotic richness are typical features of these urban waterways. This study explored the dynamics of an urban river in Cape Town by using high-resolution monitoring sensors and loggers to analyse and model real-time discharge and water quality data during and after 14 rainfall events. Discharge and water quality data were collected from the Liesbeek River at three sites during the rainfall events. As expected, the upper most sampling site had the lowest discharge and pollution load, compared to sites in the middle and lowest reaches of the river. An analysis showed significant correlations between the discharge and electrical conductivity at all three sampling sites. Rainfall was the primary factor in altering discharge and electrical conductivity. Predictive modelling using selected rainfall designs indicated that average discharge and total volume increases with increasing rainfall. Linear regression analysis for electrical conductivity indicated a strong relationship whereby an increase in discharge resulted in a decrease in electrical conductivity. This study revealed the discharge and water quality of stormwater in the Liesbeek River during rainfall events showed the improved water quality conditions in the river during the rainfall events particularly after the peak discharge. Furthermore, the implications of this study revealed that the Liesbeek River can become a water source for recharging groundwater and aquifers.